Determinants of interest free financial products in Ethiopian banking industry - Debebe Alemu Kebede (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
This study is undertaken to identify the determinants of the use and adoption of Interest free financial products in Ethiopian banking industry with specific reference to commercial banks. To achieve the aim of the study the primary data was collected from managers of some selected commercial banks through un-structured interview as well as from customers by using convenience method through standard questionnaires. While, secondary data was collected from documents of banks and Journals to triangulate with response obtained from primary data sources. The collected data was analyzed in descriptive and inferential analysis. The findings depicted as the Economic factors like unemployment and saving habits affecting the adoption of Interest free financial products and services by banks. Further, the obsoleting of technological environment, Inflexibility of government policies, Educational background of the customers and diverse cultures of the societies are the other factors that affecting adoption of financial products. In addition, the Interest free financial products and services are not properly used by the customers as the result of their low level of awareness, the perceived relative advantage, perceived compatibility and perceived complexity and perceived trust of existing banking system. Based on the result it is recommended as the banks should properly adopt the Interest free financial products and services with taking into account of the external factors. Further, the banks should participate on aggressive promotion to aware the customers about their Interest free products and services, the government should formulate policies and regulations that minimizing bureaucracy of adopting technology by banks